2021
DOI: 10.1177/02537176211045622
|View full text |Cite
|
Sign up to set email alerts
|

Companionship and Sexual Issues in the Aging Population

Abstract: Loneliness and social isolation are significant public health crises in older adults. The issues about companionship have many psychosocial and cultural dimensions, which is further compounded by the current COVID-19 pandemic. In modern-day India, there is a significant increase in the number of older adults left to live alone because of sociocultural changes in our society. Companionship in late life is known to promote the quality of life and decrease the mental health morbidity. There is an increasing role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“… Martial relationship Harmony between husband and wife Lack of relevant knowledge Lack of sexual health-related knowledge In a state of illness, there is a lack of guidance on sexual life. Ramesh et al., 2021[ 13 ], India Review Social-cultural factors Social bias: age discrimination, the older adults being asexual, and the older adults’ sexual behavior being immoral and disgusting. Health factors Physical health status: 1) disease can harm sexual organs, reduce libido, and increase fatigue; 2) drugs used to treat diseases have an impact on sexual function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Martial relationship Harmony between husband and wife Lack of relevant knowledge Lack of sexual health-related knowledge In a state of illness, there is a lack of guidance on sexual life. Ramesh et al., 2021[ 13 ], India Review Social-cultural factors Social bias: age discrimination, the older adults being asexual, and the older adults’ sexual behavior being immoral and disgusting. Health factors Physical health status: 1) disease can harm sexual organs, reduce libido, and increase fatigue; 2) drugs used to treat diseases have an impact on sexual function.…”
Section: Resultsmentioning
confidence: 99%
“…Age and senescence lead to the decline of hormone levels, which affect the changes in sexual organs and sexual functions of older adults, thus affecting sexual desire and sexual experience. Eleven of the included literature mentioned the influence of physiological factors on the sexual life of older adults, as reported by researchers [ 12 , 13 ]. There is less mucus secretion, weak ejaculation, and less semen secretion before ejaculation when men’s sexual desire declines and erections require more stimulation and last less time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand-searching of reference lists yielded 27 additional citations for screening, of which 19 met the inclusion criteria. Taking the database and hand-searches together, a total of 122 studies were included in the review , and 21 were excluded based on full-text screening [7,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213][214]. A PRISMA flow diagram of the screening process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Informed Consent Statement: Not applicable. Forward et al [196]: No data on animal companionship Gu et al [197]: Animal companionship not entered as a potential predictor variable Han [198]: Not a research study (auto-ethnographic commentary) Hunjan and Reddy [7]: No primary data Ikeuchi et al [199]: Data collected pre-pandemic Kogan et al [200]: No COVID-specific data Mayers [201]: Not a research study (auto-ethnographic commentary) McMillan et al [202]: No individual-level data Oliva and Johnston [203]: No COVID-specific data Passavanti et al [204]: No data on animals Ramesh et al [205]: No primary data Wong et al [206]: No COVID-specific data Studies found via hand-searching Arluke et al [207]: Unclear if data collected during the pandemic Aydemir et al [208]: No COVID-specific data Hargrave [209]: No primary data Hargrave [210]: No primary data Hockenhull et al [211]: No well-being data Hui Gan et al [212]: Data collected pre-pandemic Jalongo et al [213]: No primary data King [214]: No primary data…”
mentioning
confidence: 99%